Toward a Mutual Change of Religion and Urban Space: A Comparative Perspective - Ruepke, Joerg (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2023)
From a historical perspective, cities have served as more than mere locations where religious practices are observed; they have consistently exhibited an elevated level of historical documentation. The claim advanced here is that the interrelationship between religious change and urban development necessitates thorough analysis. It is imperative to critically examine the significant developments in local and trans-local religions, particularly emphasising their distinct urban contextual factors. At the same time, such urban conditions, the practices, and discourse that shape the understanding of these conditions as urban are not independent variables in the study of religious change. Rather, they are influenced by religious practices and individuals, thereby forming a reciprocal relationship. The choice of areas is an assumption that the pertinent aspect in establishing a connection is the spatial character of religious practices and ideas and their material manifestation in physical space. The article concisely examines various aspects related to the transformation of urban spaces and religious practices. These include the process of monumentalising urban areas and gods, the public display and the articulation of communication with God and gods, the imaginative and widespread utilisation of scripture in religious activities and thought, the increasing division of labour and professionalisation, the emergence of individual urban actors who are not solely defined by their ancestral lineage, the formation of religious groups, the religious organisation of time and the influence of temporal concepts on religious ideas and practices, and lastly, the conceptualisation of alternatives to urban life through the religious exaggeration of rural and natural environments. Such a cursory review of religious changes in urban settings and their impact on urbanism does not yield any definitive assertions on these developments. However, the collective evidence confirms the effectiveness of the presented approach.